Economic Impacts of the Florida Environmental Horticulture Industry in 2005 - Alan W. Hodges; John J. Haydu (EDIS)
FE675, a 40-page illustrated report by Alan W. Hodges and John J. Haydu, presents the results of an economic impact study of the Florida environmental horticulture industry conducted in 2005 and compared with previous studies in 1997 and 2000. Published by the UF Department of Food and Resource Economics, October 2006.